Diagnostic Accuracy of Cardiac Magnetic Resonance Imaging in the Detection and Characterization of Left Atrial Catheter Ablation Lesions: A Multicenter Experience. (7th January 2013) - HUNTER, ROSS J.; JONES, DANIEL A.; BOUBERTAKH, REDHA; MALCOLME‐LAWES, LOUISA C.; KANAGARATNAM, PRAPA; JULI, CHRISTOPH F.; DAVIES, D. WYN; PETERS, NICHOLAS S.; BAKER, VICTORIA; EARLEY, MARK J.; SPORTON, SIMON; DAVIES, L. CERI; et al.
<x xml:space="preserve">Abstract</x> MRI Detection of Left Atrial Ablation Lesions. Introduction: We tested the hypothesis that cardiovascular magnetic resonance (CMR) imaging can reliably distinguish the presence or absence of left atrial (LA) ablation lesions by blinded analysis of pre‐ and postablation imaging. Methods: Consecutive patients at 2 centers undergoing pulmonary vein isolation (PVI) for paroxysmal atrial fibrillation by either wide area circumferential radiofrequency ablation (WACA) or ostial ablation with a cryoballoon underwent CMR late gadolinium enhancement (LGE) imaging pre‐ and 3 months postablation. Imaging was anonymized for blinded analysis of (1) LGE images, and (2) a 3D fusion image with LGE projected onto a segmented LA surface. Scans were categorized using both assessment techniques separately as pre‐ or postablation, and if postablation, whether lesions were in an ostial or WACA distribution. Results: LGE imaging was performed in 50 patients (aged 60 ± 10 years, 68% male, 24 underwent WACA and 26 had cryoablation). Sensitivity and specificity for detection of ablation lesions was 60% and 96% on LGE imaging. Sensitivity was higher using 3D fusion imaging (88%; P = 0.003). The proportion in whom lesions were both detected and the distribution correctly assessed as WACA or ostial was higher with 3D fusion imaging compared to LGE imaging (54% vs 28%; P = 0.014). There was no difference in the detection of radiofrequency ablation lesions compared to cryoablation lesions (58% vs 62%; P = 1.000). Conclusion: LGE imaging of atrial scar is not yet sufficiently accurate to reliably identify ablation lesions or to determine lesion distribution. (J Cardiovasc Electrophysiol, Vol. 24, pp. 396‐403, April 2013)